Green Accounting, CSR Disclosure, and Profitability on Firm Value: The Moderating Effect of Firm Size in Palm Oil Companies - Henri William Dani; Keulana Erwin; Ibnu Austrindanney Sina Azhar (Economic and Business Horizon, 2026)
Growing environmental concerns and stakeholder expectations have encouraged companies to integrate sustainability practices into value creation. This study examines the effect of green accounting, Corporate Social Responsibility (CSR), and profitability on firm value, and investigates the moderating role of firm size in palm oil companies listed on the Indonesia Stock Exchange during 2018–2024. Using a quantitative approach, secondary data were collected from annual reports and financial statements of 15 palm oil companies, resulting in 105 panel observations. Panel data regression and Moderated Regression Analysis (MRA) were employed using EViews. The findings show that green accounting has no significant effect on firm value, whereas CSR disclosure and profitability have significant positive effects. Firm size has no direct effect on firm value but negatively moderates the relationship between green accounting and firm value and positively moderates the relationship between CSR disclosure and firm value. However, it does not moderate the relationship between profitability and firm value. The independent variables significantly affect firm value, highlighting the importance of CSR, sustainability transparency, and financial performance in enhancing long-term market value.